Distribution and Severity of Myopic Maculopathy Among Highly Myopic Eyes - Xiao, Ou; Guo, Xinxing; Wang, Decai; Jong, Monica; Lee, Pei Ying; Chen, Linxing; Morgan, Ian G.; Sankaridurg, Padmaja; He, Mingguang (Investigative ophthalmology & visual science, 2018)
The purpose of this study was to document the distribution of the severity of myopic maculopathy in a cohort of highly myopic patients and to explore the associated risk factors. A total of 890 Chinese highly myopes aged between 7 and 70 years (median age 19 years) and with spherical refraction -6.00 diopter (D) or worse in both eyes were investigated. All participants underwent detailed ophthalmic examination. Myopic maculopathy was graded into 5 categories according to the International Photographic Classification and Grading System using color fundus photographs: category 0, no myopic retinal lesions, category 1, tessellated fundus only; category 2, diffuse chorioretinal atrophy; category 3, patchy chorioretinal atrophy; category 4, macular atrophy. Category 2 or greater were further classified as clinically significant myopic maculopathy (CSMM). Data from 884 of 890 right eyes were available for analysis. The proportions of category 1, category 2, category 3, and category 4 were 20.0% (177 eyes), 20.2% (178 eyes), 2.6% (23 eyes), and 0.2% (2 eyes), respectively. The proportion of CSMM increased with more myopic refraction (odds ratio 1.57; 95% confidence interval: 1.46-1.68), longer axial length (odds ratio 2.97; 95% confidence interval: 2.50-3.53), and older age (40-70 years compared to 12-18 years, odds ratio 6.77; 95% confidence interval: 3.61-12.70). However, there was a higher proportion of CSMM in children aged 7 to 11 years than those aged 12 to 18 years (20.9% vs. 11.0%, P = 0.008). Older age, more myopic refraction, and longer axial length were associated with more severe myopic maculopathy. Although CSMM was uncommon among younger participants, children with early-onset high myopia have a disproportionately increased risk.